2019
DOI: 10.1364/boe.10.000670
|View full text |Cite
|
Sign up to set email alerts
|

Light-sheet microscopy with length-adaptive Bessel beams

Abstract: In light-sheet microscopy, a confined layer in the focal plane of the detection objective is illuminated from the side. The illumination light-sheet usually has a constant beam length independent of the shape of the biological object. Since the thickness and the length of the illumination light-sheet are coupled, a tradeoff between resolution, contrast and field of view has to be accepted. Here we show that scanned Bessel beams enable object adapted tailoring of the light-sheet defined by its beam length and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…In line with recent innovations to shape the light-sheet 47,48 and correct image aberrations 49 , an interesting future development of our integrated framework is to combine these innovations with laser manipulation to better resolve and target structures in the 3D space or in time.…”
Section: Discussionmentioning
confidence: 99%
“…In line with recent innovations to shape the light-sheet 47,48 and correct image aberrations 49 , an interesting future development of our integrated framework is to combine these innovations with laser manipulation to better resolve and target structures in the 3D space or in time.…”
Section: Discussionmentioning
confidence: 99%
“…Applications of the tunable DSLM demonstrated imaging analysis of medaka development from embryos to juveniles in a single scheme by adapting the beam extent to the samples. A previous study 39 reported length-adaptive Bessel beams in which the focal position and beam length of Bessel beams are automatically adapted to the samples by modulating SLM. This approach can cover samples lying over the entire FOV, but only applies to thin samples that do not fill the whole FOV.…”
Section: Discussionmentioning
confidence: 99%
“…Metasurface-based structured beams such as vortex beams [175,176], Bessel beams (see Figure 10c) [177] and Bessel beams on a fiber tip [178]. This is important for STED microscopy [179], light-sheet microscopy [180], and two-photon microscopy [181]. Fourthly, conformal metasurfaces [64,182] are another intriguing area of exploration.…”
Section: Future Directionsmentioning
confidence: 99%